The ifo Education Survey 2014-2021: A new dataset on public preferences for education policy in Germany - Vera Freundl; Elisabeth Grewenig; Franziska Kugler; Philipp Lergetporer; Ruth M. Schüler; Katharina Wedel; Katharina Werner; Olivia Wirth; Ludger Woessmann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
The ifo Education Survey is a representative opinion survey of the German voting-age population on education topics that has been conducted annually since 2014. It covers public preferences on a wide range of education policy issues ranging from early childhood education, schools, and apprenticeships to university education and life-long learning. The dataset comprises several survey experiments which facilitate investigating the causal effects of information provision, framing, and question design on answering behavior. This paper gives an overview of the survey content and methodology, describes the data, and explains how researchers can access the dataset of over 4,000 participants per wave.
Keywords: I28; D72; H52; 330; Education; policy; survey; experiment; public opinion; political economy; Germany